Girlhood interrupted: The erasure of Black girls' childhood - Epstein, Rebecca; Blake, Jamilia J.; González, Thalia (Georgetown Law, Center on Poverty and Inequality, 2017)
This groundbreaking study by the Georgetown Law Center on Poverty and Inequality provides—for the first time— data showing that adults view Black girls as less innocent and more adult-like than their white peers, especially in the age range of 5–14. The report builds on similar results that have emerged from studies of adult perceptions of Black boys. In 2014, for example, research by Professor Phillip Goff and colleagues revealed that beginning at the age of 10, Black boys are more likely than their white peers to be misperceived as older, viewed as guilty of suspected crimes, and face police violence if accused of a crime.1 SNAPSHOT OF THE DATA Compared to white girls of the same age, survey participants perceive that • Black girls need less nurturing • Black girls need less protection • Black girls need to be supported less • Black girls need to be comforted less • Black girls are more independent • Black girls know more about adult topics • Black girls know more about sex These results are profound, with far-reaching implications. Our findings reveal a potential contributing factor to the disproportionate rates of punitive treatment in the education and juvenile justice systems for Black girls.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; discipline; droit; fem3300; filles noires; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques; états-unis